Pigeonpea Crop Husbandry - International Crops Research Institute for the Semi-Arid Tropics (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This brochure is a guide to cultivating pigeonpea, covering essential aspects such as land preparation, seed rate, sowing, weed control, optimal fertilizer application and harvesting. It provides insights into managing insect pests like pod borers, pod fly, pod-sucking bugs, blister beetles and bruchids. Additionally, it addresses the control of fungal diseases like Fusarium wilt, emphasizing practices such as intercropping and crop rotation for disease prevention. Practical post-harvest handling methods are also discussed to minimize crop losses and ensure high-quality grain suitable for household consumption and market demand.